Institut cenovnih škarij - Mitrović, Dušan (Podjetje in delo, 2019)
This paper analyses diametrically diverging approaches to margin squeeze in the latest case law of the Supreme Court of the US and the Court of Justice of the EU (CJEU). Even though they were applying very similar provisions on abusive unilateral conduct and deciding cases with almost the same factual background, the CJEU repeatedly held that the margin squeeze is a type of abuse of dominant position, while the Supreme Court of the US clearly considered it as competition on merits. The main paradox of these cases is that the banning of margin squeeze most likely leads to higher prices for consumers on the downstream market, and is therefore much more beneficial to competitors than to consumers. Since a ban of margin squeeze promotes the welfare of competitors to the detriment of the consumers'' welfare, it is clear that the decision whether or not to ban it in fact implies a political decision as to whose welfare shall the competition law aim to protect. The fact that the two most developed antitrust legal systems deal with this phenomenon differently indicates different objectives of competition law in both legal systems. While the antitrust law in the US forbids only exclusionary conduct that is detrimental to consumers'' welfare, the European Commission and the CJEU interpret Article 102 of the Treaty on the Functioning of the EU (TFEU) in a way that it also prohibits exclusionary conduct that is detrimental solely to the welfare of competitors. With such interpretation, concepts of ex ante market regulation, which aim to lower the entry barriers to internal market, are being introduced to EU competition law. The latest case law of the CJEU on margin squeeze clearly shows that such "regulatory" interpretation of Article 102 TFEU interferes with the basic principle of legal certainty and reduces the consumers'' welfare.